VIRTUALIZATION OF ROMANTIC RELATIONSHIPS AND LOVE: TYPICAL EXAMPLES FROM TURKISH AND GERMAN LITERATURE - Dudu UYSAL (Fırat University, 2019)
Internet which introduces itself both as global and new media in the digital age, has created a virtual world, where people contact with each other online. An environment where i